Metal (Fe, Cu, and As) transformation and association within secondary minerals in neutralized acid mine drainage characterized using X-ray absorption spectroscopy. (April 2022) - Ye, Zhihang; Zhou, Jianwei; Liao, Peng; Finfrock, Y. Zou; Liu, YingYing; Shu, Cheng; Liu, Peng
Abstract: The formation and transformation of secondary minerals in areas affected by neutralized acid mine drainage (AMD) determine the behavior of toxic elements. To better understand the binding form of toxic elements in the secondary minerals, we focused on the distribution of secondary precipitates and heavy metals in neutralized AMD near a typical Cu-polymetallic deposit located in central Tibet. Compared to background values, the average heavy metal (As, Cu, Co, Cu, Mo, Pb, and Zn) content is higher in sediments close to the neutralized AMD drain. X-ray absorption spectroscopy (XAS) characterization shows the Fe in the suspended particulate matter (SPM) first aggregate as small Fe(III) octahedra clusters and then precipitate as ferrihydrite along the river. The XAS results also show the by-products of neutralization—ferrihydrite and sulfate—are the primary forms of Fe and S in the sediments, respectively. Gypsum retains Cu in the sediments via structural fixation, surface adsorption, and surface coprecipitation. The difference of Cu-O coordination number between the SPM and the sediments reveals the Cu sulfate coprecipitation on the surface of gypsum accompanied by SPM transporting along the river. XAS results confirm that ferrihydrite act as an essential sink for heavy metals, especially As. As(III) mineral in the sediment near the neutralized AMD outfall is dissolved and oxidized to arsenate downstream, which then adsorb to ferrihydrite and/or form As(V)-Fe minerals along the river. Gypsum and ferrihydrite have the potential to release heavy metals with changes in water chemistry, which may pose a threat to the safety of drinking water for downstream residents. The results deepen the understanding of the influence of secondary minerals (especially gypsum and ferrihydrite) on the migration and transformation process of heavy metal pollutants in mine drainage system. Graphical abstract: Image 1 Highlights: Heavy metal contents in the sediments are at a high level. High contents of gypsum and ferrihydrite precipitate in the neutralized AMD. Gypsum primarily retain Cu by coprecipitation. As(III) mineral first dissolve and then form Fe-As(V) composites. The secondary minerals exert the roles of carrier and sink of heavy metals.